AMIR TEMUR'S MILITARY TACTICS THAT SHOCKED THE WORLD - Fayzullajonova Rukhshona Mansur qizi (Western European Studies, 2025)
This article is about the military campaigns and unique tactics of Sahibkiran Amir Temur. Basically, this article reveals the essence of the Battle of Kunduz, the campaign to India and the most famous Battle of Ankara
Keywords: cavalry; burong‘or; juvong‘or